Dynamics and predictability of large-scale high-impact weather and climate events - Grotjahn, Richard; Li, Jianping; Swinbank, Richard; Volkert, Hans (Cambridge University Press, 2016)
Based largely on an International Commission on Dynamical Meteorology (ICDM) workshop, this timely volume, written by leading researchers in the field, covers a range of important research issues related to high-impact weather and extreme climate events. Dynamical linkages between these extremes and various atmospheric and ocean phenomena are examined, including Atlantic Multidecadal, North Atlantic, and Madden-Julian Oscillations; Annular Modes; tropical cyclones; and Asian monsoons. This book also examines the predictability of high-impact weather and extreme climate events on multiple time scales. Highlighting recent research and new advances in the field, this book enhances understanding of dynamical and physical processes associated with these events to help managers and policy makers make informed decisions to manage risk and prevent or mitigate disasters. It also provides guidance on future research directions in atmospheric science, meteorology, climate science, and weather forecasting, for experts and young scientists.